2020
DOI: 10.1080/13607863.2020.1830028
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic drug use and risk of mortality for people with dementia in Northern Ireland

Abstract: Objective: Anticholinergic burden refers to the cumulative effect of medications which contain anticholinergic properties. We assessed how anticholinergic burden and different types of anticholinergic medications influence mortality rates among people with dementia in Northern Ireland. Our secondary aim was to determine what demographic characteristics predict the anticholinergic burden of people with dementia. Methods: Data were extracted from the Enhanced Prescribing database for 25,418 people who were presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…No studies were found to be eligible for inclusion in this systematic review – it is therefore an ‘empty review’. This result is unexpected given that first, several studies have previously reported the risks of anticholinergic drug use and high ACB in PwD 11,29,32 and second, because evidence‐based clinical guidance has emphasised the need for high‐quality, clinical trials to evaluate interventions to reduce ACB among PwD 14 . Despite this being an empty review, we consider the findings to be important, as they highlight major gaps in the current evidence‐base and provide some indication as to the direction future research should take to guide clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…No studies were found to be eligible for inclusion in this systematic review – it is therefore an ‘empty review’. This result is unexpected given that first, several studies have previously reported the risks of anticholinergic drug use and high ACB in PwD 11,29,32 and second, because evidence‐based clinical guidance has emphasised the need for high‐quality, clinical trials to evaluate interventions to reduce ACB among PwD 14 . Despite this being an empty review, we consider the findings to be important, as they highlight major gaps in the current evidence‐base and provide some indication as to the direction future research should take to guide clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, there is a clear link between anticholinergic load and reduced cognitive performance [16][17][18]. Not only do these drugs have an impact on clinical entities such as CI, but they have also been linked to increased risk of falls [7] and mortality [24,25]. Furthermore, concomitant use of several medications with anticholinergic action will further increase the likelihood of adverse events [20].…”
Section: Discussionmentioning
confidence: 99%
“…Given that most of the drugs currently approved for the symptomatic treatment of Alzheimer's disease are aimed at restoring neuronal cholinergic activity [70], it would be contradictory to prescribe drugs whose pharmacological effect blocks this activity. Furthermore, the use of anticholinergic drugs in patients with dementia has been associated with increased mortality [25]. Therefore, in elderly patients, especially in patients with dementia [71] but also in individuals at risk such as those with subjective memory complaints [32], due to increased susceptibility to anticholinergic effects, the use of these drugs should be carefully evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, no evidence for this was found, with all associations either null or in the opposite direction to that anticipated. Other studies have found an increased risk of mortality in people with dementia taking anticholinergic drugs (McMichael et al, 2020, Tan et al, 2018. However, these studies were not restricted to specific classes of drugs such as antidepressants and antipsychotics.…”
Section: Discussionmentioning
confidence: 99%